Optimization of the internal structure of 3D-printed components for architectural restoration - Valentina Tomei; Ernesto Grande; Maura Imbimbo (Fracture and Structural Integrity)
In recent years, 3D printing technology has assumed an important role in advanced construction processes across various engineering fields. Among these, the application to the architectural restoration of historic structures is particularly fascinating. The ability to precisely reproduce the shape and surface details of complex elements, combined with the availability of a wide range of printing materials, makes 3D printing technology competitive compared to traditional techniques. In this context, the internal volume structure of 3D printed elements represents an additional design parameter to consider for enhancing interventions in terms of reducing the required material, and thus, lowering costs and environmental impact. The paper presents the outcomes of experimental tests and numerical analyses conducted on plates, which represent portions of more complex elements produced by using Additive Manufacturing (AM) technology. These plates feature various internal configurations (such as reticular and rhomboidal patterns) derived from a mono-objective design optimization process. The experimental tests aim to analyze the influence of the configuration and the pattern on the behavior of printed samples. Additionally, the paper discusses insights derived from both theoretical models and Finite Element analyses, providing a clearer understanding of the experimental results.